Parents’ and Teachers’ Perceptions of the Assessment of the Students’ English Achievement - Agustinus Ngadiman; Agnes Santi Widiati; Yohanes Nugroho Widiyanto (Widya Mandala Surabaya Catholic University, 2009)
The need for the teaching of English as a foreign language in Indonesia has been felt by almost all levels of society, especially in big cities. Without realizing the schools readiness, society has put a great expectation on the success of the English teaching. In fact, the success of the English teaching is also influenced by the parents’ involvement in the school program. Parents’ involvement will be beneficial when parents and teachers have the same perception about instructional programs, including the assessment of the students’ achievement. The study proves that parents and teachers have similar perceptions of some aspects of the English achievement assessment but different perceptions of other aspects of the assessment. In some respects, such as the function of test, the types of tests used to assess students’ English achievement, parents and English teachers are of the same perception. In other respects, however, such as the level of difficulty, the validity of the test, and the materials covered in the test, they are of different perception. This mismatch of perception may cause problems for the teachers, parents, and students.